Dr. Dania Gäng — Deep Plane Facelift — Waldshut-tiengen - Gäng, Dania (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Dania Gäng, practicing in Waldshut-tiengen, Germany. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003208; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; germany; waldshut-tiengen